Protective effects of turmeric (Curcuma longa L.) supplementation on oxidative stress and metabolic parameters in rats with high-fructose diet-induced metabolic syndrome - Ozturk, Kubra; Kocamuftuoglu, Gonca Ozan; Karatepe, Mustafa; Kisacam, Mehmet Ali; Tektemur, Nalan Kaya; Onat, Elif; Ozan, Ibrahim Enver (Springernature, 2025)
BackgroundMetabolic syndrome (MetS) is a growing global health concern characterized by oxidative stress and metabolic dysregulation. Identifying natural compounds with therapeutic potential to mitigate these effects is essential. Antioxidant parameters are crucial in reducing oxidative stress, which is a key factor in the pathophysiology of MetS.ObjectiveThis study aimed to evaluate the protective effects of turmeric (Curcuma longa L.) supplementation on oxidative stress markers, biochemical parameters, and histological outcomes in a rat model of MetS induced by a high-sugar diet.MethodsFemale Sprague-Dawley rats (n = 32) were divided into four groups: Control, metabolic syndrome (MetS-20% fructose), turmeric (80 mg/kg/day), and MetS + turmeric (80 mg/kg/day). Turmeric was administered orally for 60 days. Oxidative stress markers, lipid profiles, glucose levels, and histological changes were analyzed to assess the effects of turmeric supplementation.ResultsTurmeric supplementation significantly reduced body weight, systolic blood pressure, glucose levels, total cholesterol, low-density lipoprotein (LDL) cholesterol, and malondialdehyde (MDA) levels in MetS rats. Additionally, it increased high-density lipoprotein (HDL) cholesterol, vitamin C, vitamin A, vitamin E levels, catalase (CAT) activity, and superoxide dismutase (SOD) activity.ConclusionTurmeric supplementation at the administered dose demonstrated protective effects against the adverse impacts of a high-fructose diet in MetS development. These effects were attributed to enhanced antioxidant defense mechanisms, improved biochemical parameters, and reduced oxidative stress.
Keywords: Curcuma Longa L. (Turmeric); Liver; Metabolic syndrome; Oxidative stress; Vitamins